Effect Of Aluminium Chloride Toxicity Against Histopathology Of Gill And Liver Tissue Of Indian Major Carp, Catla Catla (Hamilton) - A.MAHARAJAN,; P.S.PARURUKMANI, (International Journal of Pharma and Bio Sciences, 2012)
Histopathological studies in organs like gill and liver of Catla catla (Hamilton) were made to assess tissue damage due to Sublethal concentration of aluminium chloride. Histopathological study provides a real picture of the detrimental effects and the involvement of the heavy metal toxicants in the major vital functions such as respiration metabolism and reproduction in aquatic animals. It is generally evident that changes in microscopic abnormalities. The gill of aluminium exposed fish exhibited vacuole formation in epithelial cells, swollen of lamellar tips, rupturing of epithelial wall, dilation of blood vessels and fusioning and shortening of secondary lamellae and loss of broken lamellar structure. The liver of Catla catla exposed to aluminium showed distinct hepatic lesions. The histopathological changes included necrosis, psychosis, disintegration of cells and vacuolization. In addition internal haemorrhage, necrosis and empty blood vessels were also seen. Such pathological changes were observed in all the tissues were more pronounced in sublethal concentration for 28 days of exposure at 10 % and 20% of the 96hrs LC50 value. The observation of the present study is to suggest that the damage of these tissues is caused by cumulative accumulation of aluminium in tissues.